G292(P) Diagnostic accuracy of the nexus II head injury clinical decision rule in children. A predict prospective cohort study. (24th May 2017) - Babl, FE; Borland, M; Phillips, N; Kochar, A; Dalton, S; Cheek, JA; Gilhotra, Y; Furyk, J; Neutze, J; Bressan, S; Donath, S; Molesworth, C; et al.
Abstract : Aims: Clinical decision rules (CDRs) can be applied in Emergency Departments (EDs) to optimise the use of computed tomography (CT) in children with head trauma. The National Emergency X- Radiography Utilisation Study II (NEXUS II) CDR, as amended for children, has not been externally validated in a large paediatric cohort. The objective of this study was to conduct a multicentre external validation of the NEXUS II CDR in children. Methods: We performed a prospective observational study of patients<18 years presenting with head trauma of any severity to 10 Australian/New Zealand EDs. In a planned secondary analysis we assessed the performance of the NEXUS II CDR for its diagnostic accuracy (with 95% confidence intervals (CI)) in predicting clinically important intracranial injury (ICI) as identified in CT scans performed in ED. Results: Of 20 137 total patients, we excluded 28 with suspected penetrating injury. Median age was 4.2 years. CTs were obtained in ED for 1962 (9.8%), of whom 377 (19.2%) had a clinically important ICI as defined by NEXUS II. 74 (19.6%) of these patients underwent neurosurgery. Sensitivity for clinically important ICI based on the NEXUS II CDR was 373/377 (98.9%; 97.3%–99.7%) and specificity 156/1585 (9.8%; 8.4%–11.4%). Positive and negative predictive values were respectively 373/ 1802 (20.7%; 18.8%–22.6%) and 156/160 (97.5%; 93.7%–99.3%). Of the 18 147 children who did not have a CT scan 49.5% had at least one NEXUS II risk criterion. Conclusions: NEXUS II had very high sensitivity when analysed with a focus on head injured patients who have had a CT performed, similar to the derivation study. With half of the unimaged patients positive for NEXUS II risk criteria the use of this CDR has the potential to increase the number of CTs.